A Se-doped MoS2 nanosheet for improved hydrogen evolution reaction. Issue 88 (21st September 2015) - Ren, Xianpei; Ma, Qiang; Fan, Haibo; Pang, Liuqing; Zhang, Yunxia; Yao, Yao; Ren, Xiaodong; Liu, Shengzhong (Frank)
Abstract : The Se-doped MoS2 was prepared via a facile annealing process and exhibited enhanced catalytic activity for hydrogen evolution reaction. Abstract : Thanks to the increase in the number of active sites and enhanced conductivity, the Se-doped MoS2 shows excellent catalytic activity with a lower overpotential of −140 mV and a smaller Tafel slope of 55 mV dec −1, exhibiting enhanced catalytic performance compared with that of pristine MoS2 . This work offers an attractive strategy to improve the HER activity of MoS2 -based catalysts.